Effects of Activities of Daily Living (ADL) Instructions on Patient with Osteoarthritis of the Knee - Nobi, MD Golam; Azad, Abul Kalam; Ahmed, Badrunnessa; Rashid, Imamur; Islam, Tariqul; Shakoor, MA (Journal of Medicine, 2012)
This prospective experimental study was done in the Department of Physical Medicine and Rehabilitation, Bangabandhu Sheikh Mujib Medical Universiry, Dhaka from 1st January 2008 to 31st July 2008 to observe the effects of ADL instructions on patients with osteoarthritis of the knee. A total of 60 patients with OA – knee were selected. Out of 60 patients 28(46.7%) were female and 32(53.3%) were male. The female to male ratio1.14:1. Age distribution varied from >40 years to <70 years with a mean age was 53.58 ± 6.86 years. Maximum patients 17(28.3%) belonged to age group of 56-60 years in both sexes and house wives were maximum in number 26 (43.3%).They were divided into two groups, 30 patients treated with therapeutic exercise plus NSAID and another 30 patients were with therapeutic exercise, NSAID and ADL. In both groups patients were treated for six weeks. In the present study, the group of patients who received NSAID, Exercise and ADL instructions improved more significantly than those who were not advised ADL instructions but received NSAID and exercise only (95% CI: 4.30 to 9.36, P = 0.001) .So, from the present study it may be concluded that activities of daily living instructions play a role to improve the symptoms of OA knee. DOI: http://dx.doi.org/10.3329/jom.v13i1.10044 JOM 2012; 13(1): 27-31